Characterising Macrophage Immunometabolism in Mycobacterium tuberculosis and HIV Co-Infection - Brown, Kevin (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Introduction Tuberculosis (TB) and HIV are leading infection-related causes of global mortality and result in an enormous amount of suffering and economic loss. Available TB treatment strategies are inadequate, and vaccination is ineffective. Treatment for HIV is lifelong, and stigma drives inaccessibility to care among those most vulnerable. The emergence of HIV has been catastrophic for global TB control programmes and TB/HIV co-infection has become a major driver of TB disease. Control of human Mycobacterium tuberculosis (Mtb) infection may rely on early immune events coordinated by the sentinel pulmonary immune cell, the alveolar macrophage (AM). HIV is known to infect AM, and AM constitute a major HIV reservoir that contributes to the resistance to eradication of infection by antiretroviral therapy. Early Mtb-induced glycolytic reprogramming in human macrophages is a central enabler of an effective host immune response, however it remains unknown whether this important metabolic shift is perturbed during concomitant chronic HIV infection. The work presented in this thesis characterises human macrophage immunometabolism during Mtb/HIV co-infection and investigates whether chronic HIV infection is likely to impair the human macrophage response to Mtb infection through altered metabolic networks. Identifying specific immune pathways that can be therapeutically targeted is an important first step in the development of novel treatment strategies that focus on supporting the host response, rather than the continued reliance on a limited supply of imperfect antimycobacterial therapies. Methods Human alveolar macrophages (AM) were harvested from bronchoalveolar lavage samples from patients who were undergoing clinically indicated bronchoscopy and consented to additional research sampling. AM were infected with virulent H37Rv Mycobacterium tuberculosis (Mtb) for 24 hr, after which time AM were lysed and RNA was isolated and purified by silica-membrane column centrifugation. Direct mRNA counting was then performed using the NanoString? nCounter? platform to generate raw count data across a targeted range of metabolic genes, which were then analysed using the NanoString? nSolver? Advanced Analysis software to characterise the metabolic transcriptional profile of virulent Mtb-infected human AM. Human U937 monocytes and their chronically HIV-1-infected U1 subclone were propagated at log phase and matured to U937 and U1 macrophages, respectively, with 48 hr PMA treatment. U937 and U1 macrophages were then infected with virulent H37Rv Mtb for 24 hr, after which time macrophages were lysed and RNA was isolated and purified by silica-membrane column centrifugation. Direct mRNA counting was performed using the same NanoString? nCounter? metabolic panel and data analysis performed using the NanoString? nSolver? Advanced Analysis software to characterise the transcriptional profile of Mtb/HIV co-infected human macrophages. Human peripheral blood mononuclear cells were isolated from buffy coats from the Irish Blood Transfusion Service and cultured in RPMI cell culture medium supplemented with human serum. Monocyte-derived macrophages (MDM) were matured by plastic adherence over six days, before gentle cold-lifting and transfer to a 24-well Seahorse XF Cell Culture Microplate. MDM were then treated with either medium control, or low or high dose HIV gp120 for 24 hr. Bioenergetic flux analysis was performed using ?-irradiated H37Rv Mtb to assess real-time MDM metabolism. Macrophage supernatants were collected following bioenergetic flux analysis and cytokine concentrations were measured using sandwich ELISA. Results Virulent Mtb induced a unique metabolic transcriptional signature in human AM, characterised by increased pro-inflammatory cytokine signalling, heightened COX2-mediated prostaglandin metabolism, induced tryptophan metabolism, and glycolytic reprogramming with reduced mitochondrial oxidative phosphorylation, consistent with Warburg metabolism. Mtb/HIV co-infected human macrophages exhibited a markedly different metabolic transcriptional profile compared to both Mtb- and HIV-infected macrophages, consistent with impaired pro-inflammatory cytokine signalling, predominantly inflammatory leukotriene-mediated arachidonic acid metabolism, and failure to induce glycolytic reprogramming. It was evident that concomitant HIV infection likely impairs early Mtb-induced changes in functional macrophage metabolism. HIV gp120 treatment of human MDM prevented immediate Mtb-induced Warburg metabolism and shifted MDM into an energetic metabolic state by significantly increasing MDM oxygen consumption rate. HIV gp120-treated MDM also exhibited a significantly reduced spare respiratory capacity after Mtb infection, indicating an impaired capacity to respond energetically to Mtb infection. HIV gp120-treated MDM failed comparatively to secrete high levels of TNF? following infection with Mtb, indicating a reduced capacity to execute effective Mtb control. Mtb-induced MDM TNF? secretion was found to be linked to mitochondrial metabolism, and specifically to flux through the electron transport chain. Inhibition of Complex I, III and V by rotenone/antimycin A and oligomycin, respectively, was found to significantly reduce Mtb-induced TNF? secretion in MDM. Prior inhibition of NAD metabolism was found to negate this effect, suggesting a role for NAD metabolism in Mtb-induced TNF? secretion in human MDM. Discussion Early events are an important opportunity for macrophage control and clearance of Mtb infection, and macrophage immunometabolism is a key paradigm in this effective early response. Despite the importance of HIV as a risk factor for complex and severe TB disease, no documented efforts have been made to characterise human macrophage metabolism in Mtb/HIV co-infection. The data presented in this thesis indicate that virulent Mtb infection induces characteristic Warburg metabolism in the sentinel pulmonary immune cell, the AM, and that concomitant human macrophage HIV infection prevents this glycolytic reprogramming, instead shifting macrophages into a more oxidative, energetic state. Impaired TNF? secretion was also a feature of co-infection. Furthermore, Mtb-induced MDM TNF? secretion was linked to mitochondrial electron transport chain flux and may be controlled by NAD metabolism. NAD depletion has been reported as a feature of both TB and HIV infection and may therefore represent a safe adjunctive therapy for patients with TB/HIV co-infection. Conclusion Global control of Mtb/HIV co-infection is an urgent necessity and novel therapies that circumnavigate current problems with antimycobacterial drug resistance must be explored as therapeutic options for people with co-infection. Understanding immune pathways that are perturbed in Mtb/HIV co-infected macrophages might enable future investigators to specifically examine therapeutic strategies that embellish the host response and improve the chances of Mtb control and the prevention of disease in those most vulnerable to severe infection.
APPROVED
Keywords: Mycobacterium tuberculosis; HIV; Human macrophage; Immunometabolism; Alveolar macrophage